2022
DOI: 10.3390/ijerph19020762
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dietary Nitrate Supplementation on Explosive Exercise Performance: A Systematic Review

Abstract: Dietary nitrate supplementation is evidenced to induce physiological effects on skeletal muscle function in fast-twitch muscle fibers and may enhance high-intensity exercise performance. An important component of sport-specific skills is the ability to perform explosive movements; however, it is unclear if nitrate supplementation can impact explosive efforts. We examined the existing evidence to determine whether nitrate supplementation improves explosive efforts lasting ≤ 6 s. PubMed, Scopus and Directory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 110 publications
(269 reference statements)
0
11
0
Order By: Relevance
“…The ergogenic effect of BRJ/NO 3 − supplementation was associated with endurance performance [ 13 ]) with an enhanced economy (reduction in VO 2 at the same intensity [ 14 ]) [ 15 ] and time-to-exhaustion [ 16 , 17 ]; but these ergogenic effects are not only for endurance performance because BRJ is an effective SS for enhancing performance in intermittent high-intensity exercise efforts [ 18 ] and explosive efforts [ 19 ]. Nevertheless, the assessment of the ergogenic effect of BRJ in the female athlete population is scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ergogenic effect of BRJ/NO 3 − supplementation was associated with endurance performance [ 13 ]) with an enhanced economy (reduction in VO 2 at the same intensity [ 14 ]) [ 15 ] and time-to-exhaustion [ 16 , 17 ]; but these ergogenic effects are not only for endurance performance because BRJ is an effective SS for enhancing performance in intermittent high-intensity exercise efforts [ 18 ] and explosive efforts [ 19 ]. Nevertheless, the assessment of the ergogenic effect of BRJ in the female athlete population is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the assessment of the ergogenic effect of BRJ in the female athlete population is scarce. In this way, a recently published systematic review on this topic showed that female participants represented only ~7% of the sample size [ 19 ]. In addition, only seven studies have analyzed the effect of BRJ on a sample composed exclusively of female athletes [ 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have indicated that dietary nitrates, typically ingested in the form of beet root juice or nitrate powder, can improve endurance [ 203 ] and explosive exercise capacity [ 204 ]. Recommended dosages generally range between 300–600 mg ingested 1–2 h prior to exercise [ 204 , 205 , 206 ].…”
Section: Some Evidence To Support Bioavailability Efficacy and Safetymentioning
confidence: 99%
“…A number of studies have indicated that dietary nitrates, typically ingested in the form of beet root juice or nitrate powder, can improve endurance [ 203 ] and explosive exercise capacity [ 204 ]. Recommended dosages generally range between 300–600 mg ingested 1–2 h prior to exercise [ 204 , 205 , 206 ]. Since nitrate can ionically bond to creatine and form a salt (see Figure 12 ), creatine nitrate (CrN) has been developed and marketed as a bioavailable source of creatine for dietary supplements [ 207 ].…”
Section: Some Evidence To Support Bioavailability Efficacy and Safetymentioning
confidence: 99%
“…The review showed that the power and velocity of certain explosive resistance exercises, along with sprint time, power output and total work in sprint studies may be affected. 38 A separate meta-analysis has also shown improvements in muscle power with isolated sprints during cycling or isokinetic knee extensions 39 and it is suggested that nitrate and nitrite can be stored in muscle tissue, potentially contributing to these improvements in power observed. 11 , 40 Thus, it seems clear that nitrate supplementation has greater potential to improve performance with higher intensity work under conditions where there is competition between oxygen demand and supply.…”
Section: Introductionmentioning
confidence: 99%